2005
DOI: 10.1016/j.joca.2005.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of knee osteoarthritis with pulsed electromagnetic fields: a randomized, double-blind, placebo-controlled study

Abstract: Applying between group analysis we were unable to demonstrate a beneficial symptomatic effect of PEMF in the treatment of knee OA in all patients. However, in patients <65 years of age there is significant and beneficial effect of treatment related to stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 20 publications
3
84
0
7
Order By: Relevance
“…PEMF as a solitary treatment for osteoarthritis of the knee has been repeatedly investigated, with confl icting results. 131,188,278,385,400 Although the eff ect of PEMFs on osteoarthritis of the knee seems equivocal, their value in the additional treatment of other bony and cartilaginous pathologies is promising. PEMFs have been proven as a successful method in fracture healing, especially in the case of nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…PEMF as a solitary treatment for osteoarthritis of the knee has been repeatedly investigated, with confl icting results. 131,188,278,385,400 Although the eff ect of PEMFs on osteoarthritis of the knee seems equivocal, their value in the additional treatment of other bony and cartilaginous pathologies is promising. PEMFs have been proven as a successful method in fracture healing, especially in the case of nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies showed EMF exposure might be useful fort he treatment of degenerative cartilage disorders such as osteoarthritis [6]. Several studies have investigated the effects of EMF on cartilage cells and tissue showing that EMF can stimulate chondrocyte proliferation and increase the amount of cartilage ECM (Extracellular matrix) components.…”
Section: General Informationmentioning
confidence: 99%
“…PEMF has now been in use for more than 3 decades and no negative side effects have been reported [15]. Four RCTs applied PEMF to the treatment of knee OA [16][17][18][19], two to patients with cervical spine OA [18,20], and one to patients with temporomandibular joint (TMJ) disorder [21]. All RCTs were double-blind treatments that used sham PEMF in the control group.…”
Section: Pulsed Electromagnetic Fieldsmentioning
confidence: 99%
“…All RCTs were double-blind treatments that used sham PEMF in the control group. The first study that used PEMF to treat knee OA included 83 patients and found significant improvements in pain and stiffness in the patients under age 65 [16]. The second knee OA study applied PEMF to 36 patients and found reduced impairment in activities of daily living and improved knee function [17].…”
Section: Pulsed Electromagnetic Fieldsmentioning
confidence: 99%